Model dan Format Media Pembelajaran Berbasis TIK Untuk Meningkatkan Minat dan Pemahaman Materi Ajar - Mohamad Miftah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Learning can be carried out well and results in mastery of the material according to general goals and special objectives as the curriculum applies, so the active role of teachers and teaching aids is needed. ICT-based learning media provide many solutions and contributions in optimizing learning and providing convenience for teachers and students. For this reason, teachers and students can be facilitated by the existence of ICT which can be integrated in learning activities. The purpose of this study is to provide an analysis of the existence of appropriate and effective ICT-based learning media models and formats in supporting teaching and learning activities. The method used is descriptive qualitative with data collection through questionnaires, interviews, observations, and documents. The sample in this study was 35 PAUD teachers by random sampling spread across Central Java. The results of the study can be said that, the model and format of ICT-based learning media that are needed and interested by teachers and according to the characteristics and facilitate students' understanding are based on; tutorials, educational games, animations, simulations, and drills.